An image registration technique to enhance PCB inspection algorithms with real images - Ibrahim, Ismail A. (2011)
It is well known that real PCD image inspection based on referential approaches faces misalignment problems in detecting defects between a template image and a defective image. Hence, a reliable image registration technique is needed to align these two images perfectly. Hence, a registration technique which incorporates affine transformation and bi-cubic interpolation has been proposed. Experimental results have shown that this registration technique is suitable to be employed to obtain well-aligned defective images before detection algorithm takes place in PCD inspection. © 2012 ICIC International.